STRENGTHENING TEENAGERS' AWARENESS ABOUT THE DANGERS OF DRUGS THROUGH ISLAMIC COUNSELING AT MADRASAH ALIYAH - Ginanjar, Taufik; Mihajra, Sugandi (Jurnal Bimbingan Penyuluhan Islam, 2025)
Drug abuse among adolescents represents an increasingly complex issue in Indonesia. It demonstrates alarming trends with serious implications for the future of the nation's younger generation. Drug prevention approaches through internalization of Islamic values become highly strategic and urgent to develop. This study aims to evaluate the effectiveness of Islamic-based counseling in enhancing adolescent resilience against drug use at MA Alhuda Pameungpeuk. Employing a mixed-methods design, the research integrates in-depth interviews, focus group discussions (FGDs), observations, and pre-test–post-test assessments using validated attitude measurement instruments. The results reveal that the internalization of Islamic values, particularly hifdz al-nafs (preservation of life) and hifdz al-ʿaql (preservation of intellect), significantly strengthens spiritual awareness, rejection attitudes, and adaptive behaviors. The discussion highlights the integration of spirituality and positive psychology frameworks in the context of drug abuse prevention through Islamic educational interventions. In conclusion, Islamic value internalization offers a promising approach in drug prevention efforts among madrasah adolescents.